Method for transporting hydrates in suspension within fluid comprising water, gas and liquid hydrocarbon, comprises incorporating fluid mixture containing component A of formed esters, and component B of non-ionic surface-active agents - AUDIBERT HAYET ANNIE; SINQUIN ANNE; DALMAZZONE CHRISTINE; PAUCHARD VINCENT (2006)
Method for transporting hydrates in suspension within a fluid comprising water, a gas and a liquid hydrocarbon (where hydrates can be formed starting from water and gas), comprises incorporating the fluid mixture containing component A of formed esters enters to a 8-24C monocarboxylic acid and 2-200C alcohol, and component B of non-ionic surface-active agents such as monocarboxylic polymerized unsaturated fatty acids. On décrit un procédé pour transporter des hydrates en suspension au sein d'un fluide comprenant de l'eau, du gaz et un hydrocarbure liquide, dans lequel on incorpore audit fluide au moins un mélange non-polluant comprenant au moins un ester, associé à un agent co-tensioactif non-ionique du type acide carboxylique polymérisé (dimère et/ou trimère).La composition est introduite en général à une concentration de 0,1 à 5 % en masse par rapport à l'hydrocarbure liquide.